The Effect of Using the Strategy of Similarities in Improving the Reading Comprehension Skills of the Sixth Grade Female Students in the North-West Badia Educational Directorate in Jordann - القاضي كفاح; هيثم القاضي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study aims at identifying the effect of using the strategy of similarities in improving the reading comprehension skills of the sixth grade female students in the North-West Badia educational Directorate in Jordan. The participants of the study were (30) sixth grade female students from Al-Za’atri Secondary School for Girls in the North-West Educational Directorate for the scholastic year (2021-2022). The participants were selected by the available way and they were divided randomly into two groups: experimental and control ; each group consisted of (15) students. The researcher used the quasi-experimental method and prepared an achievement test in reading comprehension which consisted of (15) essay questions; (5) for literal comprehension, (5) for inference comprehension and (5) for critical comprehension. The results showed that there is a statistically significant difference at ɑ =0.05% in the favor of the experimental group.